Forest conservation support communication (FCSC) for community forest development in South Western Nigeria (2003)
The paper reports the prospect of both the institutional structure and personnel capabilities of government agencies responsible for rural development at impacting Forest Conservation Support Communication (FCSC) on the inhabitants of three conservation areas - Old Oyo National Park and Oluwa and Shasha forest reserves in southwestern Nigeria. The study was carried out with the aid of' structured questionnaires administered on the agricultural extension and, forest personnel of the states under which the conservation areas fall. The study reveals that 51.9% of the extension personnel in southwestern Nigeria are holders of university degrees/higher diplomas and 32.6% of them had put in more than 15 years of cognate service. However, only.2.8% of them claim to be forest extension workers. Apart from Oyo State where each personnel was in contact with more than 100 Farmers/month, others make contact with between 20 and 100/month. The study also reveals that although the communication capabilities o f change agents were not in doubt, their knowledge of forestry as well as their agencies' capabilities were near-nil. It is therefore recommended that a separate unit for forestry extension need be created in each of the states under study.